2021
DOI: 10.3389/fimmu.2021.725129
|View full text |Cite
|
Sign up to set email alerts
|

Repertoire of Naturally Acquired Maternal Antibodies Transferred to Infants for Protection Against Shigellosis

Abstract: Shigella is the second leading cause of diarrheal diseases, accounting for >200,000 infections and >50,000 deaths in children under 5 years of age annually worldwide. The incidence of Shigella-induced diarrhea is relatively low during the first year of life and increases substantially, reaching its peak between 11 to 24 months of age. This epidemiological trend hints at an early protective immunity of maternal origin and an increase in disease incidence when maternally acquired immunity wanes. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…This observation also suggests that Shigella infection is not only dependent on the presence of that organism but is determined by other host-related factors, such as maternal immunity (i.e., antibodies in breast milk) and the individual’s own local innate defenses. We and others have identified placentally acquired maternal antibodies to Shigella antibodies at birth ( 16 , 17 , 41 ). Shigella -specific antibodies have been found in breast milk ( 61 ).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…This observation also suggests that Shigella infection is not only dependent on the presence of that organism but is determined by other host-related factors, such as maternal immunity (i.e., antibodies in breast milk) and the individual’s own local innate defenses. We and others have identified placentally acquired maternal antibodies to Shigella antibodies at birth ( 16 , 17 , 41 ). Shigella -specific antibodies have been found in breast milk ( 61 ).…”
Section: Discussionmentioning
confidence: 91%
“…Participants were recruited as part of a mother-infant cohort in a malaria surveillance study ( 41 ). All of the infants were born between February and November of 2016.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IcsA holds great vaccine candidate potential because it was demonstrated previously that the level of antibodies to IcsA significantly reduces the risks of shigellosis ( 38 ). High levels of anti-IcsA antibodies were also found as one major maternal antibody transferred to the infant and may likely contribute to disease prevention during the first months of life ( 39 ). The correlated protection is likely to be through the prevention of early Shigella host cell attachment as was demonstrated previously ( 11 ) with adhesion-blocking activity by anti-IcsA antibodies and not through antibody-mediated complement killing ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Serotype specificity is determined by the OAg of LPS, therefore immune responses targeting the OAg are likely responsible for protection against shigellosis. Although the OAg-specific immune response has traditionally been quantified by antigen-specific IgG detection through ELISA, presumably a functional readout, such as opsonophagocytosis and/or complement activation, can better determine the effectiveness of antibodies raised upon vaccination [ 32 ]. A recent study reported a strong association between S. flexneri 2a-specific SBA titers in human adult volunteers and reduced clinical disease post-challenge with wild-type organisms [ 13 ], thus supporting the value of this assay to potentially predict vaccine efficacy.…”
Section: Discussionmentioning
confidence: 99%